2023
DOI: 10.3389/fphar.2023.1244098
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pleiotropic effects of direct oral anticoagulants on cultured endothelial cells: a comprehensive review

Natalia Atzemian,
Dimitra Kareli,
Georgia Ragia
et al.

Abstract: Direct Oral Anticoagulants (DOACs) have simplified the treatment of thromboembolic disease. In addition to their established anticoagulant effects, there are indications from clinical and preclinical studies that DOACs exhibit also non-anticoagulant actions, such as anti-inflammatory and anti-oxidant actions, advocating overall cardiovascular protection. In the present study, we provide a comprehensive overview of the existing knowledge on the pleiotropic effects of DOACs on endothelial cells (ECs) in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…As mentioned above, preclinical studies showed anti-inflammatory, antioxidant and anti-fibrotic effects on endothelial cells. Importantly, several studies highlighted DOAC-mediated effects on endothelial cells in terms of improvement in endothelial function and integrity and the inhibition of neo-angiogenesis [ 22 , 39 , 40 ]. Although peculiar effects of a single molecule have not yet been determined, it is generally accepted that factor Xa inhibitors produce anti-angiogenic and anti-fibrotic effects beyond the anti-inflammatory action and stabilization of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned above, preclinical studies showed anti-inflammatory, antioxidant and anti-fibrotic effects on endothelial cells. Importantly, several studies highlighted DOAC-mediated effects on endothelial cells in terms of improvement in endothelial function and integrity and the inhibition of neo-angiogenesis [ 22 , 39 , 40 ]. Although peculiar effects of a single molecule have not yet been determined, it is generally accepted that factor Xa inhibitors produce anti-angiogenic and anti-fibrotic effects beyond the anti-inflammatory action and stabilization of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of DOACs to regulate PAR responses provides new insights into their actions beyond anticoagulation. Indeed, several preclinical studies demonstrated that DOACs exhibit pleiotropic actions on endothelial cells such as anti-inflammatory, anti-atherosclerotic and anti-fibrotic effects, as well as the preservation of endothelial integrity [ 19 , 20 , 21 , 22 ]. It has been established that DOACs block some pro-inflammatory processes, regulating the expression of some key cytokines in a plethora of in vitro cell systems [ 22 ] as well as in animal models of atherosclerotic lesions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, there is evidence that the activation of PAR signaling in the heart plays a pivotal role in cardiac inflammation, fibrotic response, and repair processes [ 31 ]. DOACs, by inhibiting factor Xa and thrombin, are recognized for preventing PAR signaling activation, thereby extending their effects beyond thromboembolism [ 2 ] []. Recent findings also propose that DOACs may deter atrial remodeling in rats through PAR signaling inhibition [ 32 ] and ameliorate cardiac fibrosis in AF mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the anticoagulant effect of DOACs is exerted via the inhibition of blood clotting. Since thrombin is well known to activate protease-activated receptor (PAR) signaling, DOACs potentially exert effects beyond anticoagulation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%